The Influence of Future Package Financing (PMD) and Facilitator Assistance on Women's Empowerment in Developing Family Economy: A Sharia Microfinance Perspective (Case Study on BTPN Syariah Customers in Medan Labuhan) - Yeni Yolanda; Imsar Imsar; Tuti Anggraini (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This research aims to analyze the influence of the Future Package Financing (PMD) program and the role of facilitator assistance on women's empowerment in developing family economics among BTPN Syariah customers in the Medan Labuhan area. The research method used is a quantitative approach with an associative design, involving 97 respondents selected through purposive sampling techniques and analyzed using multiple linear regression via SPSS software. The research results show that PMD Financing and Facilitator Assistance, both partially and simultaneously, have a positive and significant effect on women's empowerment, with regression coefficients of β1 = 0.315 (t = 4.125, p < 0.05) for PMD Financing and β2 = 0.339 (t = 4.428, p < 0.05) for Facilitator Assistance, indicating that Facilitator Assistance has a relatively stronger influence compared to the financing variable. The combination of these two variables is able to explain 65.4% of the changes in the level of family economic empowerment (R2 = 0.654). In conclusion, access to capital supported by capacity building through intensive assistance is the main key in realizing the economic independence of female customers. It is recommended that BTPN Syariah enhance the frequency and quality of financial management training modules during Sentra group meetings and consider incentive-based financing schemes for customers with good repayment records to maximize the impact of the empowerment program. Future research is expected to incorporate external macro factors and broader geographic coverage to strengthen generalizability.